Cornelia de Lange syndrome: from molecular diagnosis to therapeutic approach. Issue 5 (8th November 2019) - Sarogni, Patrizia; Pallotta, Maria M; Musio, Antonio
Abstract : Cornelia de Lange syndrome (CdLS) is a severe genetic disorder characterised by multisystemic malformations. CdLS is due to pathogenetic variants in NIPBL, SMC1A, SMC3, RAD21 and HDAC8 genes which belong to the cohesin pathway. Cohesin plays a pivotal role in chromatid cohesion, gene expression, and DNA repair. In this review, we will discuss how perturbations in those biological processes contribute to CdLS phenotype and will emphasise the state-of-art of CdLS therapeutic approaches.